The Role of the Regional Financial and Asset Agency in the Reconciliation of Central Tax Collection on Regional Expenditure Government of North Sumatra Province First Semester of Fiscal Year 2025 - Febri Muliansyah; Syafruddin Ritonga; Maksum Syahri Lubis (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of the Regional Financial and Asset Agency (BKAD) of North Sumatra Province in the reconciliation of central tax collection on regional expenditure during the first semester of Fiscal Year 2025, as well as to identify the inhibiting factors in its implementation. The research employs a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and documentation involving informants from BKAD officials, central tax authorities, and regional financial management officers. Data analysis is conducted using the interactive model of Miles and Huberman. The results indicate that BKAD has carried out its role as a coordinator, facilitator, and controller in the implementation of central tax reconciliation on regional expenditure; however, the implementation has not yet been fully optimal. The main inhibiting factors include limited technical understanding of taxation among officials, delays in data submission, and the lack of integration between regional financial information systems and central tax systems. Therefore, strengthening human resource capacity, improving information systems, and enhancing inter-agency coordination are required to support the effectiveness of central tax reconciliation on regional expenditure.